The Effect of Madrasah Head Leadership Effectiveness and Work Motivation on Teacher Performance in the Special Region of West Papua - Adzidzah, Nur; Yudiawan, Agus (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
The study aims to determine: (1) an overview of the level of effectiveness of madrasah head leadership, teacher work motivation and teacher performance; (2) the effect of work motivation on teacher performance; (3) the effect of the effectiveness of the leadership of the head of the madrasa on the performance of teachers; (4) the effect of the effectiveness of the leadership of the madrasa head and the motivation of work together on the performance of teachers in MI, MTs, and MA Emeyodere. This study used a quantitative approach with a population of all MI, MTs, and MA Emeyodere teachers of 29 people. The sampling technique used is a saturated sample where all members of the population are sampled. The data were collected by disseminating questionnaires and subsequently analyzed by multiple regression analysis. The results showed that: (1) the effectiveness of the leadership of the head of the madrasah in the good category (3.79), the work motivation of teachers in the sufficient category (2.66), and the performance of teachers in the sufficient category (2.70) on a scale of 5.00; (2) There is a positive and significant influence of work motivation on teacher performance with a regression coefficient of +0.329; (3) There is a positive and significant influence of the effectiveness of the madrasa head's leadership on teacher performance with a regression coefficient of +0.68; and (4) There is a positive and significant influence on the effectiveness of madrasa head leadership and work motivation together on teacher performance in MI, MTs, and MA Emeyodere with the regression line equation obtained Y = 1.138 + 0.329 X1 + 0.681 X2.